Juridical Analysis of The Use of Artificial Intelligence in Handling The Crime of Sexual Harassment in Cyberspace - Efi Nurnaningsih; Taufik Firmanto; R Ridwan; S Syamsuddin; Aman Maarij; M. Farizan Islam (Proceeding International Conference Restructuring and Transforming Law, 2024)
The increase in information technology crime is increasingly widespread, where people use this technology as a means to violate the law. Information technology has influenced and encouraged changes in the social and economic needs of society. This research focuses on how to preventively control sexual violence on social media. As well as the role of artificial intelligence in preventing some applications that are often misused by some parties to find victims who can be harassed, with the Electronic Information and Transaction Law in sexual violence. The method / approach used is the normative method by looking for literature journal articles, and relevant sources. The results of this study include.1. This harassment occurs due to a lack of sex education and a lack of morality from individuals so that they do things that violate the norms of decency and norms of decency, the lack of education from these individuals is the cause of sexually harassing behavior; 2. artificial intelligence that will search for content that smells of child sexual abuse on the internet. Google Content Safety API uses a network to scan photos by making images that are considered inappropriate less conspicuous; 3. Replacing and/or tracking using electronic systems against people who are objects in electronic information/documents for sexual purposes. This research is expected to be a solution in dealing with sexual violence on social media.